Pemphigus Vulgaris; [Pénfigo Vulgar] - Fuenzalida-Cruz, H; Pereira-Rudolph, F (Ediciones Doyma, S.L., 2024)
Pemphigus vulgaris is an uncommon dermatological pathology with a relevant importance due to its morbidity and mortality. It presents fragile blisters on the skin, mucosal erosions, involvement of the cranial skin and in some cases nail damage. Although its symptoms may be diverse, some manifestations help us suspect it and act in time. Its study and diagnostic confirmation is with biopsy and immunofluorescence. Finally, its treatment represents a challenge, despite achieving remission of the lesions, this pathology has common recurrences. In the following review, we will show three clinical cases and analysis of the clinical manifestations with their differential diagnoses. © 2024 Elsevier España, S.L.U.